Insulation protection oxalic acid anodizing method
By performing the first overall thin-oxalic acid and two nickel acetate seals on the surface of the aluminum alloy, a non-porous, dense oxalic acid anodized film layer is formed, and the second local oxalic acid anodization is carried out, the edge film layer layer is solved. and block loss defects, the film layer has improved its breakdown resistance and local strengthening effect.
Patent Information
- Application Number
- CN202411627125.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-07
AI Technical Summary
The existing oxalic acid anodizing process is prone to film layer delamination and block loss defects at the edges of the parts, making it difficult to guarantee the requirements for smooth and sharp edges, and cannot effectively solve the problem of local reinforcement of the parts.
The first method of monoporous oxalic acid and two nickel acetate sealing was used to form a non-porous, dense oxalic acid anodized film layer on the surface of the aluminum alloy, and local reinforcement was performed through the second local oxalic acid anodization.
The oxalic acid anodized film layer with improved insulation breakdown resistance is formed, which avoids the collapse and layering at the edges, achieves the effect of local strengthening and increasing the thickness of the film layer, and at the same time improves the pass rate of the process.
Smart Images

Figure CN119392332A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material surface treatment, and in particular relates to a method for insulating protective oxalic acid anodizing. Background Art
[0002] Oxalic acid anodizing technology is widely used in valve and bushing product components. Generally, the valve and bushing mating surfaces are required to be oxalic acid anodized (overall oxalic acid anodizing is allowed) because the oxalic acid anodized film is wear-resistant and has high hardness. However, the final state of the parts requires that the edges of the outer circle of the valve and the inner hole of the bushing are smooth and sharp, and the parts are matched to size. The current traditional process flow is as follows: machining - degreasing - pickling - overall oxalic acid anodizing (including the working surface of the part) - machining and grinding to the size and appearance required by the design drawing. The existing process flow and process methods have disadvantages. After oxalic acid anodizing, although a high-hardness and wear-resistant oxalic acid anodized film is obtained on the working surface of the part, during the oxidation process, due to the brittleness of the oxalic acid anodized film itself and the large internal stress, the hardness difference between the film and the substrate is large. In addition, the edge film growth of the non-working surface and the working surface of the part is vertical growth, which squeezes each other (such as Figure 2 ). Film delamination is easy to occur at the edges of parts, and the brittleness of the film layer at the edges increases sharply. After subsequent machining and grinding, sharp edge collapse defects are very likely to occur at the edges, making it difficult to meet the requirements of smooth and sharp edges.
[0003] The Chinese patent publication number is CN113981500A, and the name is a patent application for an oxalic acid anodizing process for hard aluminum alloy shell parts. The step-by-step voltage-boosting method is introduced to adjust and match the oxidation voltage, oxidation time, voltage-boosting speed, and frequency of the electrolytic cell, so that the appearance, film thickness, and insulation resistance of the oxalic acid anodized film formed on the surface of the shell parts meet the standard acceptance requirements, with a high pass rate, which completely solves the low pass rate of oxalic acid anodizing of hard aluminum shells, greatly reduces the problem of scrapped parts caused by film ablation and black spots, and ensures the consistency of insulation resistance of different parts of the shell parts. This patent application can improve the quality of the oxalic acid anodized film of the shell parts, but the method used in this patent application cannot solve the problem of local strengthening of parts and the operation is complicated. However, this patent application cannot solve the problem of film layer delamination and block drop defects that are prone to occur on the edges. Summary of the invention
[0004] In order to overcome the problems existing in the above-mentioned prior art, the purpose of the present invention is to provide a method for insulating protective oxalic acid anodizing, which can form a non-porous and dense oxalic acid anodized film layer on the surface of the aluminum alloy through the method of the first overall thin oxalic acid and two nickel acetate sealing, thereby improving the insulation breakdown resistance and being able to be locally strengthened through the second local oxalic acid anodizing.
[0005] To achieve the above object, the technical solution adopted by the present invention is: A method for insulating and protecting oxalic acid anodizing, comprising the following steps: The parts to be treated are subjected to oxalic acid anodizing as a whole; Use high-temperature nickel salt solution to perform the first sealing treatment on the entire part; The thin oxalic acid anodized film layer of the working surface that needs to be locally anodized with oxalic acid is removed by grinding; Use high-temperature nickel salt solution to perform a second sealing treatment on the entire part; Carry out local oxalic acid anodizing on the working surface that requires local oxalic acid anodizing.
[0006] Optionally, the parts to be treated are cleaned with a degreasing solution before oxalic acid anodizing.
[0007] Optionally, when performing oxalic acid anodization, a mixed solution of sulfuric acid and oxalic acid is used, wherein the mass ratio of sulfuric acid to oxalic acid is 5:1.
[0008] Optionally, when performing an oxalic acid anodizing treatment on the entire part, a constant current anodizing treatment is used for 15-35 minutes; when performing an oxalic acid anodizing treatment on a part, a constant current anodizing treatment is used for 120-150 minutes.
[0009] Optionally, the nickel salt solution is a nickel acetate solution.
[0010] Optionally, the concentration of the nickel acetate solution is 7.5-15 g / L.
[0011] Optionally, the time of the first sealing treatment and the second sealing treatment are both greater than or equal to 15 minutes, and the temperature is both 90 to 100°C.
[0012] Optionally, during the oxalic acid anodizing, compressed air is used for stirring.
[0013] Optionally, after the local oxalic acid anodizing is completed, the parts are blown dry by compressed air.
[0014] Optionally, during oxalic acid anodizing, titanium alloy tooling is used to mount the parts.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a method for insulating protective oxalic acid anodizing, through the method of first overall thin oxalic acid and twice nickel acetate sealing, a non-porous and dense oxalic acid anodized film is formed on the surface of the aluminum alloy, and the insulation breakdown resistance is improved; through the second local oxalic acid anodizing, the oxide film thickness can reach 60-80 microns without leakage; and the voltage does not breakdown at 60-90V, and local strengthening can be achieved. The method for insulating protective oxalic acid anodizing of the present invention can prevent the occurrence of block collapse at the edge of the oxalic acid anodized film after subsequent mechanical processing and grinding, which affects the smoothness required by the design requirements.
[0016] The present invention is not directly used for insulation protection in the oxalic acid anodizing process, but can greatly reduce the delamination and falling of the oxalic acid anodizing film after the parts machining workshop is finished. The present invention has strong controllability, and there is no leakage of the oxalic acid anodizing film on the non-working surface. Figure 5 As shown, the qualified rate of the method of the present invention is increased from 50% of the traditional method to 85%. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The drawings described herein are for explanation purposes only and are not intended to limit the scope of the present invention in any way. In addition, the shapes and proportional dimensions of the components in the drawings are only for illustration purposes to help understand the present invention, and are not intended to specifically limit the shapes and proportional dimensions of the components of the present invention. In the drawings: Figure 1 It is a schematic diagram of the process of the present invention; Figure 2 Schematic diagram of the growth of edge film during oxalic acid anodization; Figure 3 This is a schematic diagram of a bushing part according to an embodiment of the present invention; Figure 4 This is a schematic diagram of valve parts according to an embodiment of the present invention; Figure 5 It is a bar graph of the qualified rate of the present invention. DETAILED DESCRIPTION
[0018] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0019] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] In the description of the embodiments of the present invention, it should be noted that if the terms "upper", "lower", "horizontal", "inner", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the accompanying drawings, or is the orientation or position relationship in which the product of the invention is usually placed when used. It is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0021] The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only embodiments. If the term "horizontal" appears, it does not mean that the component is required to be absolutely horizontal, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0022] It should be noted that similar reference numerals and letters represent similar items in the following figures, so once an item is defined in one figure, it does not need to be further defined and explained in the subsequent figures. In the description of the present invention, it is understood that the terms "include" and "comprise" indicate the presence of the described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the technical field of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. As used in the specification of the present invention and the appended claims, the singular forms of "a", "an" and "the" are intended to include plural forms unless the context clearly indicates otherwise.
[0024] The present invention is described in detail below with reference to the accompanying drawings.
[0025] The present invention relates to a process of oxalic acid anodizing with a thin oxalic acid anodizing film layer (7-17 μm) as insulation protection, and in particular to an oxalic acid anodizing insulation protection process for aluminum and aluminum alloy parts. The present invention mainly aims at the phenomenon of delamination and falling of the edges of the parts after the whole oxalic acid anodizing, and explores a new oxalic acid anodizing process, which can not only meet the requirements of the drawings for oxalic acid anodizing of the working surface, but also prevent the occurrence of collapse and delamination of the oxalic acid anodizing film layer on the edges of the parts.
[0026] like Figure 1 As shown, a method for insulating and protecting oxalic acid anodizing of the present invention comprises the following steps: The parts to be treated are subjected to oxalic acid anodizing as a whole; Use high-temperature nickel salt solution to perform the first sealing treatment on the entire part; The thin oxalic acid anodized film layer of the working surface that needs to be locally anodized with oxalic acid is removed by grinding; Use high-temperature nickel salt solution to perform a second sealing treatment on the entire part; The working surface that needs to be locally oxalic acid anodized is locally oxalic acid anodized, wherein the working surface that needs to be locally oxalic acid anodized is determined according to the design drawing.
[0027] The present invention forms a non-porous and dense oxalic acid anodized film layer on the surface of the aluminum alloy by first overall thin oxalic acid coating and two nickel acetate sealing methods, and the insulation breakdown resistance is improved; the oxide film thickness can reach 60-80 microns without leakage through the second local oxalic acid anodizing; and the voltage does not breakdown at 60-90V. The insulation protection oxalic acid anodizing method of the present invention can prevent the occurrence of block collapse at the edge of the oxalic acid anodized film layer after subsequent mechanical processing and grinding, and affect the smoothness required by the design requirements.
[0028] Example 1 A method for insulating and protecting oxalic acid anodization in this embodiment includes the following steps: 1) Cleaning the parts to be treated with a degreasing solution; specifically, the parts to be treated are parts that require oxalic acid anodizing of the outer circle or inner hole.
[0029] Optionally, the part to be processed is a valve or a bushing.
[0030] 2) The cleaned parts to be processed are mounted on a titanium alloy tooling and subjected to oxalic acid anodizing. The solution used in the oxalic acid anodizing is a mixed solution of sulfuric acid and oxalic acid.
[0031] Specifically, the mass ratio of sulfuric acid to oxalic acid is 5: 1. The oxalic acid anodizing temperature is 12-15° C. and the mixture is stirred with compressed air.
[0032] The oxalic acid anodizing process adopts constant current anodizing treatment; the constant current oxidation treatment includes increasing the current to the process specified current within 5 minutes, and maintaining the oxidation treatment at the constant current for 15-35 minutes; 3) First sealing treatment: Sealing solution: nickel acetate, concentration: 7.5-15g / L, temperature: 90-100℃, time: ≥15 minutes.
[0033] Nickel salt reacts with water to generate nickel hydroxide which is deposited in the pores of the aluminum oxide film, thus filling the pores of the oxide film. Compared with the unsealed oxalic acid anodized film layer, the pressure resistance of the film layer will be greatly improved, thus playing a better role in insulation protection. In addition, the high-temperature nickel acetate sealing solution has a better effect than the strong temperature sealing solution, and the pores are more tightly blocked.
[0034] 4) The thin oxalic acid anodized film layer on the working surface that needs a second local oxalic acid anodizing is removed by mechanical processing such as grinding the inner hole or grinding the end surface.
[0035] The inspection is to check whether the original color of the base aluminum is exposed by visual inspection and to measure the size to detect whether the film layer has been removed completely.
[0036] 5) Second sealing treatment: Sealing solution: nickel acetate, concentration: 7.5-15g / L, temperature: 90-100℃, time: ≥15 minutes.
[0037] The reason for adopting secondary nickel acetate high temperature sealing is to better increase the pressure resistance of the oxalic acid anodized film layer on the non-working surface and prevent the oxalic acid anodized film layer on the non-working surface from being broken down after the secondary oxalic acid anodizing.
[0038] 6) The parts after secondary sealing are locally anodized with oxalic acid, wherein the solution used for the anodization with oxalic acid is a mixed solution of sulfuric acid + oxalic acid (in a ratio of 5:1).
[0039] The oxalic acid anodizing temperature is 12-15°C, and the compressed air is used for stirring. The oxalic acid anodizing process adopts constant current oxidation treatment; the constant current oxidation treatment includes increasing the current to the process specified current within 5 minutes, and maintaining the oxidation treatment at the constant current for 120-150 minutes.
[0040] 7) Blow the product obtained in step 6) dry with compressed air to prevent the film from being oxidized and from being stained with dirt before drying.
[0041] 8) Send metallographic examination for thickness and hardness inspection. The thickness of the oxalic acid anodized film on the working surface is required to be 60-80μm and the hardness ≥350HV 0.01, The inspection was carried out on the appearance and no leakage of the oxalic acid anodized film was found on the non-working surface.
[0042] 9) Use a CNC grinder to grind the oxalic acid anodized film on the working surface.
[0043] 10) Machining inspection: There is no chipping or delamination of the oxalic acid anodized film on the working surface after machining and grinding.
[0044] Example 2 This embodiment selects Figure 3 30 bushing parts are used as the parts to be processed; in this embodiment, the bushing parts are made of 6061 aluminum alloy, the B and C surfaces are working surfaces, and the other surfaces are non-working surfaces. The overall area of a single piece is 0.6dm 2 The sum of the areas of surface B and surface C is 0.15dm 2 , the implementation steps are as follows: 1) Use titanium alloy tooling to install the bushing parts.
[0045] 2) Clean the bushing parts to be treated with degreasing solution for 30-60 seconds.
[0046] 3) Use nitric acid with a concentration of 300-500g / L to corrode for 0.3-3 minutes to remove the substances generated after degreasing and expose the clean metal surface.
[0047] 4) The bushing parts were anodized with oxalic acid using a mixed solution of sulfuric acid and oxalic acid in a mass ratio of 5:1. The oxalic acid anodizing temperature was 12°C. The current was increased to 31A within 5 minutes. The oxidation treatment was maintained at a constant current for 15 minutes to obtain an oxalic acid anodized film with an average thickness of 10.3 μm.
[0048] 5) The obtained parts are subjected to the first sealing treatment, the sealing solution is 7.5g / L nickel acetate, the treatment temperature is 90°C, and the treatment time is: 15 minutes.
[0049] 6) Use mechanical processing to remove the thin oxalic acid anodized film on the surface of B and C; 7) The obtained parts are subjected to a second sealing treatment, the sealing solution is 7.5g / L nickel acetate, the treatment temperature is 90°C, and the treatment time is 15 minutes.
[0050] 8) The obtained parts were locally anodized with oxalic acid, the current was increased to 7.7A within 5 minutes, and the oxidation treatment was maintained at a constant current for 120 minutes.
[0051] 9) Dry the parts with compressed air.
[0052] 10) Send the metallographic examination for thickness and hardness test. The working surface oxalic acid anodized film thickness is required to be 70μm and the hardness is 395HV0.01. The inspection is to check the appearance. There is no leakage of oxalic acid anodized film on the non-working surface.
[0053] 11) Use a CNC grinder to grind the oxalic acid anodized film on the working surface.
[0054] 12) Machining inspection: After machining and grinding, the oxalic acid anodized film on the working surface has basically no block collapse or delamination. The results are shown in Table 1 below.
[0055] Table 1
[0056] Example 3 This embodiment selects Figure 3 30 bushing parts are used as the parts to be processed; in this embodiment, the bushing parts are made of 6061 aluminum alloy, the B and C surfaces are working surfaces, and the other surfaces are non-working surfaces. The overall area of a single piece is 0.6dm 2 The sum of the areas of surface B and surface C is 0.15dm 2 , the implementation steps are as follows: 1) Use titanium alloy tooling to install the bushing parts.
[0057] 2) Clean the bushing parts to be treated with degreasing solution for 30-60 seconds.
[0058] 3) Corrosion: 0.3-3 minutes.
[0059] 4) The bushing parts were anodized with oxalic acid using a mixed solution of sulfuric acid and oxalic acid in a mass ratio of 5:1. The oxalic acid anodizing temperature was 15°C. The current was increased to 31A within 5 minutes. The oxidation treatment was maintained at a constant current for 35 minutes to obtain an oxalic acid anodized film with a thickness of 10.3 μm.
[0060] 5) The obtained parts are subjected to the first sealing treatment, the sealing solution is 15g / L nickel acetate, the treatment temperature is 100°C, and the treatment time is: 15 minutes.
[0061] 6) Use mechanical processing to remove the thin oxalic acid anodized film on the surface of B and C; 7) The obtained parts are subjected to a second sealing treatment, the sealing solution is 15g / L nickel acetate, the treatment temperature is 100°C, and the treatment time is 15 minutes.
[0062] 8) The obtained parts were locally anodized with oxalic acid, the current was increased to 7.7A within 5 minutes, and the oxidation treatment was maintained at a constant current for 150 minutes.
[0063] 9) Dry the parts with compressed air.
[0064] 10) The metallographic examination was conducted for thickness and hardness test. The thickness of the oxalic acid anodized film on the working surface was required to be 78μm and the hardness was 387HV0.01. The appearance was checked and there was no leakage of the oxalic acid anodized film on the non-working surface.
[0065] 11) Use a CNC grinder to grind the oxalic acid anodized film on the working surface.
[0066] 12) Machining inspection: After machining and grinding, the oxalic acid anodized film on the working surface has basically no block collapse or delamination. The results are shown in Table 2 below.
[0067] Table 2
[0068] Example 4 This embodiment selects Figure 4 There are 30 valve parts. In this embodiment, the material of the valve parts is 6061 aluminum alloy, the B and C surfaces are working surfaces, and the other surfaces are non-working surfaces. The overall area of a single piece is 0.32dm 2 , the sum of the areas of surfaces B and C is 0.1dm 2 , the implementation steps are as follows: 1) Use titanium alloy tooling to install the valve parts.
[0069] 2) Clean the valve parts to be treated with degreasing solution for 30-60 seconds.
[0070] 3) Corrosion: 0.3-3 minutes.
[0071] 4) The valve parts were anodized with oxalic acid using a mixed solution of sulfuric acid and oxalic acid in a mass ratio of 5:1. The oxalic acid anodizing temperature was 13°C. The current was increased to 16.3A within 5 minutes. The oxidation treatment was maintained at a constant current for 20 minutes to obtain an oxalic acid anodized film with a thickness of 10.8 μm.
[0072] 5) The obtained parts are subjected to the first sealing treatment, the sealing solution is 10g / L nickel acetate, the treatment temperature is 96°C, and the treatment time is: 20 minutes.
[0073] 6) Use mechanical processing to remove the thin oxalic acid anodized film on the surface of B and C; 7) The obtained parts are subjected to a second sealing treatment, the sealing solution is 10g / L nickel acetate, the treatment temperature is 96°C, and the treatment time is 20 minutes.
[0074] 8) The obtained parts were locally anodized with oxalic acid, the current was increased to 5.1 A within 5 minutes, and the oxidation treatment was maintained at a constant current for 130 minutes.
[0075] 9) Dry the parts with compressed air.
[0076] 10) The metallographic examination was conducted for thickness and hardness test. The thickness of the oxalic acid anodized film on the working surface was required to be 69μm and the hardness was 401HV0.01. The appearance was checked and there was no leakage of the oxalic acid anodized film on the non-working surface.
[0077] 11) Use a CNC grinder to grind the oxalic acid anodized film on the working surface.
[0078] 12) Machining inspection: The oxalic acid anodized film on the working surface showed basic collapse and delamination after machining. The results are shown in Table 3 below.
[0079] Table 3
[0080] Unless otherwise specified, the device elements involved in the above embodiments are all conventional device elements, and the structural settings, working modes or control modes involved are all conventional settings, working modes or control modes in the art unless otherwise specified.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in the field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for insulating and protecting oxalic acid anodizing, characterized in that: The following steps are involved: The parts to be treated are subjected to oxalic acid anodizing as a whole; Use high-temperature nickel salt solution to perform the first sealing treatment on the entire part; The thin oxalic acid anodized film layer of the working surface that needs to be locally anodized with oxalic acid is removed by grinding; Use high-temperature nickel salt solution to perform a second sealing treatment on the entire part; Carry out local oxalic acid anodizing on the working surface that requires local oxalic acid anodizing.
2. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: Before oxalic acid anodizing, clean the parts to be treated with a degreasing solution.
3. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: When performing oxalic acid anodizing, a mixed solution of sulfuric acid and oxalic acid is used, wherein the mass ratio of sulfuric acid to oxalic acid is 5:
1.
4. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: When the whole part is anodized with oxalic acid, constant current anodizing is used for 15-35 minutes; when the part is locally anodized with oxalic acid, constant current anodizing is used for 120-150 minutes.
5. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: The nickel salt solution is a nickel acetate solution.
6. The method for insulating protective oxalic acid anodizing according to claim 5, characterized in that: The concentration of the nickel acetate solution is 7.5-15 g / L.
7. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: The time of the first sealing treatment and the second sealing treatment are both greater than or equal to 15 minutes, and the temperature is both 90 to 100°C.
8. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: When performing oxalic acid anodizing, compressed air is used for stirring.
9. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: After the local oxalic acid anodizing is completed, the parts are blown dry by compressed air.
10. The method for insulating protective oxalic acid anodizing according to claim 1, characterized in that: When performing oxalic acid anodizing, titanium alloy tooling is used to mount the parts.
Citation Information
Patent Citations
Oxalic acid anodic oxidation process method for hard aluminum alloy shell part
CN113981500A